Taikonauts prepare for liftoff [Chinese manned space programme]. - Oberg, J.
In this paper, the author describes how China's manned space program is only the tip of the iceberg in its bid to challenge the space status quo. He explains how, with a manned space program as the centerpiece of its strategy, China may well become a force to be reckoned with in orbit
Keywords: China; Taikonauts; Manned space program